Principles of Polymer Design and Synthesis - Su, Wei-Fang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
How can a scientist or engineer synthesize and utilize polymers to solve our daily problems? This introductory text, aimed at the advanced undergraduate or graduate student, provides future scientists and engineers with the fundamental knowledge of polymer design and synthesis to achieve specific properties required in everyday applications. In the first five chapters, this book discusses the properties and characterization of polymers, since designing a polymer initially requires us to understand the effects of chemical structure on physical and chemical characteristics. Six further chapters discuss the principles of polymerization reactions including step, radical chain, ionic chain, chain copolymerization, coordination and ring opening. Finally, material is also included on how commonly known polymers are synthesized in a laboratory and a factory. This book is suitable for a one semester course in polymer chemistry and does not demand prior knowledge of polymer science.
Introduction -- Polymer Size and Polymer Solutions -- Structure, Morphology and Flow of Polymers -- Chemical and Physical Properties of Polymers -- Characterization of Polymers -- Step Polymerization -- Radical Chain Polymerization -- Ionic Chain Polymerization -- Coordination Polymerization -- Chain Co-Polymerization -- Ring-Opening Polymerization.
Keywords: Chemistry; Polymers; Industrial engineering; Surfaces (Physics).; Chemistry; Polymer Sciences; Industrial and Production Engineering; Characterization and Evaluation of Materials